Kebahagiaan (Happiness) Siswa yang Berasal dari Keluarga Ibu Single Parent - Hanifah Pratiwi; Riska Ahmad (Universitas Negeri Padang, 2020)
This research is motivated by the phenomenon of junior high school students where students here are faced with an incomplete family condition that affects various things such as not being able to accept incomplete family understanding, difficult to accept criticism from others, feeling less attention from their ecpecially family from their parents, does not have confidence in the crowd, often withdraws and prefers to be alone, lacks motivation to learn, cannot build good relationships with the environment. This study aims to describe how the happiness of students who come from single mother families based on several aspects, namely: (1) acceptance (2) affection (3) achievement. This type of research is quantitative with a descriptive approach. The subjects in this study were 51 students at SMPN 15 Padang who came from single mother families. The research instrument was a happiness questionnaire. The data were processed using descriptive statistical analysis techniques and proportion techniques: The results showed that (1) the happiness of students who came from single mother families, seen from the aspect of acceptance, was generally in the happy category with a proportion of 64.7%, (2) student happiness those who come from single mother families, seen from the aspect of affection, are generally in the happy category with a proportion of 51%, (3) the happiness of students who come from the mother's family, seen from the aspect of achievement, are generally in the very happy category with the proportion of 47.1%.